2006
DOI: 10.1007/s10517-006-0222-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-arginine on various types of pain sensitivity

Abstract: Intraperitoneal injection of L-arginine to male Wistar rats 12 min before the start of the experiment produced a nociceptive effect on models of electrocutaneous stimulation of the tail or hot-plate test and increased nociceptive behavior due to high sensitivity of supraspinal nociceptive structures to this compound. The nociceptive effect of this amino acid was more pronounced and persistent under conditions of electrocutaneous stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…There is evidence for the analgesic effect of L-arginine. The analgesic effect of L-arginine in patients with persistent pain has long been known [ 41 ] and L-arginine supplementation can prevent allodynia and hyperalgesia in painful diabetic neuropathic rats [ 42 ] and the nociceptive effect of L-arginine could be pronounced and persistent in rats [ 43 ]. L-arginine can improve the clinical symptoms of intermittent claudication in patients with peripheral arterial occlusive disease [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence for the analgesic effect of L-arginine. The analgesic effect of L-arginine in patients with persistent pain has long been known [ 41 ] and L-arginine supplementation can prevent allodynia and hyperalgesia in painful diabetic neuropathic rats [ 42 ] and the nociceptive effect of L-arginine could be pronounced and persistent in rats [ 43 ]. L-arginine can improve the clinical symptoms of intermittent claudication in patients with peripheral arterial occlusive disease [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an animal model, arginine was shown to increase pain sensitivity. 53 Clinical trials of arginine in painful human conditions have produced contradictory findings. In some studies, local arginine application in combination with calcium carbonate has been shown to be beneficial in the treatment of dentine hypersensitivity, 54 – 56 although the mechanism is related to physical sealing of dentin tubules with a plug that is resistant to pulpal pressures and acid challenge.…”
Section: Arginine In Painmentioning
confidence: 99%